THE ROLE AND EFFECT OF TELEGRAM AND KAHOOT PLATFORMS IN EFL CLASSROOMS - Anvarjon Isroilov G‘iyosidinovich (TADQIQOTLAR, 2026)
Annotation This study investigates the effectiveness of Telegram and Kahoot platforms in English as a Foreign Language (EFL) classrooms. The research focuses on their impact on students’ motivation, engagement, and language skill development, particularly in grammar and vocabulary acquisition. A mixed-method approach was employed, including classroom observation, questionnaires, and pre-test/post-test analysis. The findings reveal that the integration of these digital tools significantly enhances student participation, improves vocabulary retention, and creates a more interactive and engaging learning environment. Telegram supports continuous learning beyond the classroom, while Kahoot promotes active participation through gamified assessment. The study concludes that combining these platforms contributes to more effective and student-centered EFL instruction.